Anomaly detection using one-class SVM with wavelet packet decomposition - Hautakangas, Hannu; Nieminen, Jukka (2011)
Anomaly detection has become a popular research topic in the field of machine learning. Support vector machine is one anomaly detection technique and it is coming one the most widely used. In this research, anomaly detection is applied to road condition monitoring, especially pothole detection, using accelerometer data. The proposed concept includes data preprocessing, feature extraction, feature selection and classification. Accelerometer data was first filtered and segmented, after which features were extracted with frequency- and time-domain functions, with genetic programming and with wavelet packet decomposition. A classification model was built using support vector machine and the calculated features. The results with actual accelerometer data demonstrates that potholes can be detected reliably. Features from wavelet packet decomposition yielded the best classification results.